Revealing that artificial reproduction promotes increased genetic diversity between generations in Carpinus putoensis - Li, Dingsheng; Gao, Kai; Chen, Yeping; Gao, Haojie; Huang, Haiming; Ye, Bo; Shi, Lei; Yu, Haina; Zhao, Ying (Frontiers in Plant Science, 2025)
IntroductionCarpinus putoensis, an endemic species of Putuo Island in the Zhoushan Archipelago, Zhejiang Province, China, is listed as critically endangered (D1) in the 1998 World List of Threatened Trees.MethodsUsing 15 pairs of SSR primers markers, 143 individuals from three population generations were analyzed, generating 193 alleles.Results and DiscussionThe average number of alleles (Na) was 12.9, ranging from 4 to 28, while the average effective number of alleles (Ne) was 4.900, with a range of 1.649 to 11.602. The multilocus outcrossing rate (tm) was 1.000, and the single-locus outcrossing rate (ts) was 0.871, ranging from 0.751 to 0.920 across the families studied. The difference between tm and ts (0.129) and the positive biparental inbreeding coefficients (0.080 to 0.249) indicate the presence of inbreeding. Moreover, an increase in Na and Ne was observed across generations, from 6.400 and 2.838 in the F1 generation to 9.200 and 4.228 in the F3 generation, respectively. These results highlight the need for artificial interventions to increase population size and improve genetic diversity, which are critical factors for the conservation and recovery of C. putoensis.